1992
DOI: 10.1007/bf00010354
|View full text |Cite
|
Sign up to set email alerts
|

Growth of peach as affected by decomposition of own root residues in soil

Abstract: The effects of decomposing peach root residues in soil on peach growth were determined in two pot experiments. In the first, peach root residues, despite their high C:N ratio and lignin content, largely decomposed under experimental conditions, leading to an immobilization of inorganic N. Shoot growth of peach seedlings was depressed by the addition of peach root residues, an effect that depended on their size and concentration: fine-textured root fragments (0.45-1.00mm) resulted in more severe effects than me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In agreement with several previous laboratory studies (Patrick, 1971 ; Putnam et al ., 1983 ; Rice, 2012 ), we found that fresh litter causes severe and acute damage to A. glutinosa roots after 72 h of exposure. Most previous works have recorded the inhibitory effects of fresh litter in laboratory bioassay or, in a few cases, in pot experiments with litter added to the soil (Tagliavini & Marangoni, 1992 ; Van der Putten et al ., 1997 ; Dorrepaal, 2007 ). Here, we further provide evidence of the inhibitory effect of fresh litter, extending this evidence to aquatic roots of a riparian tree.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with several previous laboratory studies (Patrick, 1971 ; Putnam et al ., 1983 ; Rice, 2012 ), we found that fresh litter causes severe and acute damage to A. glutinosa roots after 72 h of exposure. Most previous works have recorded the inhibitory effects of fresh litter in laboratory bioassay or, in a few cases, in pot experiments with litter added to the soil (Tagliavini & Marangoni, 1992 ; Van der Putten et al ., 1997 ; Dorrepaal, 2007 ). Here, we further provide evidence of the inhibitory effect of fresh litter, extending this evidence to aquatic roots of a riparian tree.…”
Section: Discussionmentioning
confidence: 99%